2019
DOI: 10.1111/joa.12991
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic allometry and architectural properties of the paravertebral and hindlimb musculature in Eastern cottontail rabbits (Sylvilagus floridanus): functional implications for developmental changes in locomotor performance

Abstract: Due to small body size, an immature musculoskeletal system, and other growth-related limits on performance, juvenile mammals frequently experience a greater risk of predation than their adult counterparts. As a result, behaviorally precocious juveniles are hypothesized to exhibit musculoskeletal advantages that permit them to accelerate rapidly and evade predation. This hypothesis was tested through detailed quantitative evaluation of muscle growth in wild Eastern cottontail rabbits (Sylvilagus floridanus). Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, ontogenetic scaling analysis showed that hindimb P musc scaled to body mass at a rate needed to maintain “mechanical similarity” (i.e., maintenance of functional capacities across growth-related increases in size; Carrier 1983 ) ( Fig. 7 E; P musc = 2.2M b 1.32 [1.240, 1.404] , R 2 : 0.98; mechanical similarity prediction = M b 1.33 ; also see Butcher et al. (2019) ), indicating that the superior mass-specific power capacities of juvenile rabbits were more likely due to their smaller overall size than more powerful muscles per se .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, ontogenetic scaling analysis showed that hindimb P musc scaled to body mass at a rate needed to maintain “mechanical similarity” (i.e., maintenance of functional capacities across growth-related increases in size; Carrier 1983 ) ( Fig. 7 E; P musc = 2.2M b 1.32 [1.240, 1.404] , R 2 : 0.98; mechanical similarity prediction = M b 1.33 ; also see Butcher et al. (2019) ), indicating that the superior mass-specific power capacities of juvenile rabbits were more likely due to their smaller overall size than more powerful muscles per se .…”
Section: Resultsmentioning
confidence: 99%
“…7 E), the superior performance of juveniles is most likely due to their absolutely smaller body size. Seen in this light, the ontogenetic allometry of the S. floridanus musculoskeletal system may be more indicative of the need for adults to keep pace with juveniles, rather than the converse ( Butcher et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to variation in animal condition and motivation, and occasional equipment malfunction, we were only able to collect locomotor performance data in 42 rabbits. Of the animals contributing locomotor performance data, we euthanized 14 animals for detailed anatomical study, including measurements of r for several hindlimb extensor muscles and fiber architecture (see below; Butcher et al, 2019). The sample for the present study consists of a subset of 13 individuals for whom we obtained sufficient kinematic and morphological data to calculate EMA.…”
Section: Animal Capture and Assessmentmentioning
confidence: 99%